THE FACTORS WHICH INFLUENCE THE CAPACITY TO ORGANIZE FINANCIAL STATEMENT OF SKPD WITH INTERNAL CONTROL AS MODERATING VARIABLE IN BINJAI MUNICIPALITY - sutarsih, wiwik (Asosiasi Dosen Akuntansi Indonesia, 2018)
The objective of the research was to analyze some factors which influenced the capacity to organize the financial statements in the Regional Government Work Unit with internal control as moderating variable in Binjai Municipality. This is an analytical survey research. The population was the financial administration officials and treasurers of expenditure, i.e. 33 regional government work units in Binjai Municipality. The data were gathered through 66 questionnaires distributed to the financial administration officials and treasurers of expenditure. The samples were taken by employing census method in which the whole population was taken as the samples for this research. The data analysis method was assisted by Smart PLS program (Structural Equation Modeling Partial Least Square/ SEM PLS). The results of the research demonstrated that quality of human resources did not have any positive influence; understanding of governmental accounting system did not have any positive influence; the use of regional financial information system had a positive influence and internal control had a positive influence on the ability in administering financial statements. Internal control as moderating variable could not moderate the influence of human resource quality on the capacity to organize financial statements; the influence of the understanding of governmental accounting system and the use of regional financial information system on the capacity to organize financial statements